Barriers and facilitators to physical activity promotion by healthcare professionals: an umbrella review - Rui Hu; Kehan Li; Jinde Liu; Stanley Saichuen Hui; Donting Yun; Zihan Dai; Di Tang; Yanyan Xu (BMC Public Health, 2026)
Abstract Background Physical inactivity is consistently associated with the incidence of chronic diseases. The clinical environment may be an ideal setting to promote physical activity (PA). To date, substantial efforts have been made by multiple institutions to encourage PA promotion by healthcare professionals. Nevertheless, the implementation of PA promotion in clinical practice remains suboptimal. This review aimed to identify barriers and facilitators influencing healthcare professionals’ promotion of PA, and to develop recommendations for its future implementation, guided by the Theoretical Domains Framework (TDF) and the Capability-Opportunity-Motivation-Behavior (COM-B) model of the Behavior Change Wheel (BCW). Methods A comprehensive search of five databases (PubMed, Web of Science, Scopus, PsycINFO, CINAHL Full-Text) was conducted to identify relevant articles. Any type of review that reported factors related to healthcare professionals' PA promotion was included. Barriers and facilitators were extracted and mapped to the TDF and the COM-B model of the BCW by one investigator on the basis of established definitions, and were then verified by a second investigator, with disagreements resolved through discussion or consultation. The identified TDF domains were then linked to corresponding BCW intervention functions (e.g., education, persuasion, incentivization) and policy categories (e.g., communication/marketing, guidelines, fiscal) to inform future practice. The quality of each review was appraised using the revised Joanna Briggs Institute Critical Appraisal Checklist for Systematic Reviews and Research Synthesis. Results A total of 18 studies were included for final analysis. The majority were systematic reviews and/or meta-analyses, which analyzed studies using quantitative, qualitative, and mixed-methods designs. In total, 83 themes pertaining to facilitators and 90 themes pertaining to barriers were identified. The most prominent facilitator domains were ‘social influences’, ‘knowledge’, and ‘social/professional role and identity’. In contrast, the most frequently reported barrier domains were ‘knowledge’, ‘environmental context and resources’, and ‘social influences’. Intervention functions of ‘education’, ‘training’, ‘restriction’ and ‘environmental restructuring’, along with policy categories such as ‘guidelines’, ‘regulation’, and ‘legislation’, may support PA promotion among healthcare professionals. Conclusions This review highlighted several barriers faced by healthcare professionals, and further identified eight intervention functions as well as seven policy categories. Future studies might explore implementation issues from other perspectives. Registration This review was pre-registered on PROSPERO (CRD420251167125): https://www.crd.york.ac.uk/PROSPERO/view/CRD420251167125 .